(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Human papillomavirus (HPV) poses significant health risks globally, being a primary cause of cervical cancer (CC) and other malignancies. CC remains a leading cause of morbidity and mortality among women in Saudi Arabia, with an incidence rate of 1.9/100,000 women. Previous studies have indicated a general lack of awareness surrounding HPV and its vaccine among the Saudi population. Objective: This study aimed to assess knowledge, awareness, and HPV vaccine acceptance among females in Saudi Arabia. Methods: A cross-sectional study was conducted from July 2024 to March 2025, enrolling Saudi females aged 12 years and older through questionnaires. A total of 798 participants were included, comprising both medical professionals and the general public. Variables of interest included demographic information, knowledge levels regarding HPV, and attitudes toward HPV vaccination. Results: Among participants, 74.7% reported awareness of HPV, with the internet being the most referenced information source (37.1%). However, significant gaps were identified: 50.6% were unaware that HPV can be asymptomatic, and 60.2% lacked knowledge regarding its association with various cancers. Only 3.3% had undergone HPV testing, while 48% recognized the vaccine’s potential to prevent CC and genital warts. Notably, 69.2% expressed willingness to receive the vaccine if offered for free, and 83.7% supported educational interventions to enhance awareness. Knowledge levels correlated significantly with age, education, and income, with 37.8% demonstrating low knowledge levels and only 34.1% showing high knowledge regarding HPV. Conclusion: The study reveals a mixed understanding of HPV and its vaccine among Saudi women, highlighting significant gaps in knowledge despite a generally positive attitude toward vaccination. Enhanced educational outreach and targeted interventions are crucial to improve awareness and acceptance of the HPV vaccine, thereby supporting public health initiatives aimed at reducing HPV-related disease incidence.